2020
DOI: 10.1101/2020.06.18.20134353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-13 is a driver of COVID-19 severity

Abstract: Here we report on an inpatient cohort of COVID-19 positive patients where plasma cytokines were tested for association with future need for mechanical ventilation. Hierarchical clustering, Kaplan-Meier curves, and odds ratios demonstrated that two cytokines, IL-13 (OR: 1.57) and IL-7 (OR: 1.04) and the growth factor bFGF (OR: 1.04), were predictive for intubation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…Moreover, our analysis shows that TMPRSS2 expression is not altered by interferon Accordingly, it has recently been reported that interferon inflammation does not modulate TMPRSS2 expression but upregulates ACE2 expression [12]. Instead, TMPRSS2 expression in airway epithelia is highly upregulated by IL-13 [12,14], a highly expressed cytokine in plasma of COVID-19 patients that require ventilation [13]. Furthermore, IL-13 is also involved in allergic airway type 2 inflammation, asthma and chronic obstructive pulmonary disease (COPD) [12,14], thus suggesting a further mechanism for COVID-19 susceptibility and severity.…”
Section: Analysis Of Tmprss2 Expression Datamentioning
confidence: 49%
“…Moreover, our analysis shows that TMPRSS2 expression is not altered by interferon Accordingly, it has recently been reported that interferon inflammation does not modulate TMPRSS2 expression but upregulates ACE2 expression [12]. Instead, TMPRSS2 expression in airway epithelia is highly upregulated by IL-13 [12,14], a highly expressed cytokine in plasma of COVID-19 patients that require ventilation [13]. Furthermore, IL-13 is also involved in allergic airway type 2 inflammation, asthma and chronic obstructive pulmonary disease (COPD) [12,14], thus suggesting a further mechanism for COVID-19 susceptibility and severity.…”
Section: Analysis Of Tmprss2 Expression Datamentioning
confidence: 49%
“…Considering the novelty of COVID-19 pathophysiology, we aimed to include all possible and detectable abnormalities and therefore used the CheXNeXT system that can accurately identify 14 different pathologies. In this context, it is noteworthy that using cytokine/chemokine data on hospitalised patients with COVID-19, Donlan et al 11 have shown that circulating concentration of interleukin-13 (IL-13) can predict the need for mechanical ventilation. Since IL-13 can contribute to pulmonary eosinophilia and tissue remodelling, it is thus possible that radiographically detectable texture alterations that are neither captured by the RALE score nor the CheX-NeXT system may accompany these cytokine profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The established and validated CheXNeXt deep learning algorithm 10 as well as the PXR network 11 are based on the DenseNet121 12 architecture. While the CheXNeXt predicts one or more of 14 lung pathologies from an X-ray image of the chest, the PXR network scores an X-ray image for severity of acute respiratory distress syndrome (ARDS).…”
Section: Network Architecturementioning
confidence: 99%
“…An alternative hypothesis suggests a central role for bradykinin in the inflammation and increased vascular permeability observed in COVID-19 [ 104 ]. Respiratory failure appears to be associated in particular with a type 2 immune response, typified by IL-13 production, which is higher in patients requiring mechanical ventilatory support [ 105 ]. Although type 2 immune responses are protective in the gut [ 106 , 107 ], they are deleterious in the lung [ 108 ].…”
Section: Clinicalmentioning
confidence: 99%